The size-dependent non-localized deformation in a metallic alloy. (May 2015) - Zhong, C.; Zhang, H.; Cao, Q.P.; Wang, X.D.; Zhang, D.X.; Jiang, J.Z.
Abstract : The tensile behaviors of Cu50 Zr50 metallic glass (MG) films with the same cooling history as a function of film thickness are systematically studied by molecular dynamics simulations. It clearly reveals that with decreasing film thickness, a transition from the localized deformation to the non-localized deformation indeed occurs in Cu50 Zr50 MG films, which might be a general phenomenon for all MGs. The thickness-dependent deformation mode change observed here, is then reasonably explained by the Griffith crack-propagation criterion.